Semiological Dichotomies of Signification - boudjellal, elrabia (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract :This article aims to define the direction of semantic semiology, which took upon itself the study of the non-linguistic sign, in which Barth wanted to prove that semiology derived its procedural concepts from linguistics. In this direction, he focused on linguistic dualities and how Barth applied them to the system (food, clothing, and furniture) in the semiological system..